Some Experiences in Neuromarketing: Moving from White Papers to Scientific Inquiries - Diaz-Munoz, H (Elsevier B.V., 2021)
The objective of this paper is to show the added value of using tools such as eyetracking, galvanic skin response, facial coding and others in the field of market research and user experience research. We will present 3 case studies in which these tools have been used successfully. We will give an overview of the background, the objectives, methods and results and how the neuro-tools provided additional insights into consumer behaviour, which would otherwise not have been possible. In this paper we will specifically show cases from packaging design, advertising research and user experience research thus only covering a small part of possible application areas. © 2021 The Authors. Published by Elsevier B.V.